Violence against women : myths, facts, controversies - DeKeseredy, Walter S., 1959- (University of Toronto Press, 2011)
In Violence Against Women, award-winning author Walter S. DeKeseredy offers a passionate but well-documented sociological overview of a sobering problem. He starts by outlining the scope of the challenge and debunks current attempts to label intimate violence as gender neutral. He then lays bare the structural practices that sustain this violence, leading to a discussion of long- and short-term policies to address the issue. DeKeseredy includes an examination of male complicity and demonstrates how boys and men can change their roles. Throughout, he responds to myths that dismiss threats to women's health and safety and provides an impassioned call to action for women, men, and policymakers